ACTIVE AND PASSIVE VOICE IN ENGLISH (Modern education and development, 2024)
This article examines the grammatical structures of active and passive voice in English, exploring their syntactic properties, uses, and functions within different contexts. Active voice, where the subject performs the action, is generally preferred for its clarity and directness. In contrast, passive voice emphasizes the recipient of the action, often obscuring the subject or when the doer is unknown or unimportant. This study outlines the transformations between active and passive constructions, highlighting the role of transitive verbs and the auxiliary verb "to be" in passive sentences. Additionally, the article discusses the application of both voices in academic writing, legal texts, and everyday communication, emphasizing how the choice between active and passive voice impacts readability, tone, and focus. Through examples and linguistic analysis, the paper aims to provide a comprehensive understanding of how these voice structures shape the expression of actions in the English language.